Macroeconomic modeling and policy analysis for less developed countries - "Khayum, Mohammed F." (Boulder, 1991)
This book provides an overview of macro econometric modeling for less developed countries, a description of the structure and performance of Guyana's economy, an empirical testing of the model using annual data for Guyana, and a simulation approach to policy evaluation.
Keywords: Economics